Effect of a zinc oxide nanoparticle fuel additive on the emission reduction of a hydrogen dual-fuelled engine with jatropha methyl ester biodiesel blends. (20th November 2016) - Javed, Syed; Satyanarayana Murthy, Y.V.V.; Satyanarayana, M.R.S.; Rajeswara Reddy, R.; Rajagopal, K.
Abstract: Emissions from a Direct Injection (DI) diesel engine can be reduced by the addition of metallic fuel-borne additives. However, the effect of fuel-borne catalysts in a dual fuel engine with hydrogen (H2 ) as a secondary fuel is not well known. Hence, experimentation was carried out to investigate the effects of nano-metallic oxide fuel additives on the major physicochemical properties and performance of jatropha biodiesel blends in a DI diesel engine in dual fuel mode. Jatropha methyl ester (JME) biodiesel is produced from degummed crude jatropha oil after reducing the free fatty acid (FFA) content to less than 2% and performing transesterification using a 20 kHz frequency ultrasonicator with a sodium hydroxide (NaOH) catalyst. Zinc oxide (ZnO) nanoparticles at 100 ppm with a size of 20 and 40 nm were suspended in primary fuel of JME biodiesel. H2 as a secondary fuel with flowrates of 0.5 and 1.5 L/min was maintained during the experiments. The experimental results reveal that the nanoparticle size influences the engine performance and emissions. The presence of nanoparticles in the fuel blends reduced the nitrogen oxide (NOx ) emissions. However, the effects of the size and concentration were marginal with an increasing H2 flowrate. With an increasing H2 flow rate, hydrocarbon (HC) emissions decreased for nanoparticles of size 20 nm, but increased for 40 nm. Smoke opacity was increased compared with pure biodiesel owing to the presence of surfactant Triton-X100. Highlights: H2 biodiesel dual fuelled diesel engine studies with nano additives. ZnO nanoparticles 20 & 40 nm and H2 flowrate of 0.5 & 1.5 L/min were studied. The size of nanoparticle additives influences performance of the engine. NOx reduced from 450 to 320 ppm of biodiesel blended with ZnO nano additive. 11% reduction in smoke opacity when the H2 flowrate is increased to 1.5 L/min.